Is Small Beautiful? Size Effects of Volatility Spillovers for Firm Performance and Exchange Rates in Tourism - Chia-Lin Chang; Hui-Kuang Hsu; Michael McAleer (Tinbergen Institute, 2013)
This paper examines the size effects of volatility spillovers for firm performance and exchange rates with asymmetry in the Taiwan tourism industry. The analysis is based on two conditional multivariate models, BEKK-AGARCH and VARMA-AGARCH, in the volatility specification. Daily data from 1 July 2008 to 29 June 2012 for 999 firms are used, which covers the Global Financial Crisis. The empirical findings indicate that there are size effects on volatility spillovers from the exchange rate to firm performance. Specifically, the risk for firm size has different effects from the three leading tourism sources to Taiwan, namely USA, Japan, and China. Furthermore, all the return series reveal quite high volatility spillovers (at over sixty percent) with a one-period lag. The empirical results show a negative correlation between exchange rate returns and stock returns. However, the asymmetric effect of the shock is ambiguous, owing to conflicts in the significance and signs of the asymmetry effect in the two estimated multivariate GARCH models. The empirical findings provide financial managers with a better understanding of how firm size is related to financial performance, risk and portfolio management strategies that can be used in practice.
urn:NBN:nl:ui:15-1765/38230
Keywords: C22; G32; L83; 330; Tourism; Size effects; Small-firm effects; Financial performance; Spillover effects; MGARCH; VARMA; BEKK; Konjunktur; Wechselkurs; Volatilität; Betriebsgröße; Spillover-Effekt; ARCH-Modell; Tourismuswirtschaft; Taiwan